2021
DOI: 10.1186/s10152-021-00553-0
|View full text |Cite
|
Sign up to set email alerts
|

In the Asia-Pacific region, the COI DNA test revealed the divergence of the bivalve mollusc Mactra chinensis into three species; can these species be distinguished using shell coloration and sperm structure?

Abstract: According to COI DNA barcoding testing, the marine bivalve mollusc Mactra chinensis, which is native to the Asia-Pacific region, diverged into three species. These species were preliminary characterized as M. chinensis COI clade I, M. chinensis COI clade II and M. chinensis COI clade III. To find out whether it is possible to morphologically distinguish samples representing genetic clades, we examined the color of the shells and the structure of the spermatozoa. It was found that the number of detected colorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Different shell colors resulting from phenotypic plasticity due to environmental factors are indistinguishable by genetic information. It was found that three genetic species of Mactra chinensis could not be determined reliably based on analysis of the shell coloration due to the plasticity of these morphological characters (Reunov et al, 2021); in Corbicula population, morphotypes defined by internal shell color were indistinguishable in genetic background (Li et al, 2022), and there are also examples of different species with the same shell color (Williams et al, 2016), different species of marine snails Clanculus pharaonius and Clanculus margaritarius were examined that contained different pigments but produced similar colors. This fact shows that there may be some adaptive value for these colors and patterns despite differences in their habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Different shell colors resulting from phenotypic plasticity due to environmental factors are indistinguishable by genetic information. It was found that three genetic species of Mactra chinensis could not be determined reliably based on analysis of the shell coloration due to the plasticity of these morphological characters (Reunov et al, 2021); in Corbicula population, morphotypes defined by internal shell color were indistinguishable in genetic background (Li et al, 2022), and there are also examples of different species with the same shell color (Williams et al, 2016), different species of marine snails Clanculus pharaonius and Clanculus margaritarius were examined that contained different pigments but produced similar colors. This fact shows that there may be some adaptive value for these colors and patterns despite differences in their habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Hen clam (Mactra chinensis) is a clam species widely found in the soft sandy bottom of the upper subtidal and intertidal zones of the coastal areas of Russia, Korea, Taiwan and Japan [1]. According to the results of a cytochrome coxidase I (COI) DNA investigation, hen clams living in the Asia-Pacific region can be categorized into three types of species [2]. In Korea, they are abundant in the low and mid-intertidal zones of the west and south coasts, within a depth range of approximately 10 m; around Jeju Island, they are only known to be found off the coast of Gwakjiri, a village in the town of Aewol (Eup).…”
Section: Introductionmentioning
confidence: 99%